Estimates and projections in the economic impacts of fifteen dietary risk factors for two hundred four countries and territories from 2020 to 2050: a health-augmented macroeconomic modeling study - Li, Yiyuan; Du, Xihao; Wu, Yiping; Xu, Xiangyun; Chen, Simiao; Cao, Zhong; Wang, Jingxuan; Huang, Yue; Rong, Shuang; Zhong, Victor W (The American journal of clinical nutrition, 2025)
Background - Suboptimal diet results in significant health and economic burdens. However, the global economic costs of dietary risks remain unclear. - Objectives - This study aimed to estimate the macroeconomic burden of 15 dietary risk factors in 204 countries and territories from 2020 to 2050. - Methods - This health-augmented macroeconomic modeling study assessed the macroeconomic burden that accounted for the decrease in labor supply across different education levels due to mortality and morbidity, as well as the impact of healthcare expenses on investment and savings. Country-specific data were drawn from publicly accessible databases. The cumulative difference in the aggregate output between a realistic scenario without intervention and a counterfactual scenario assuming complete disease elimination was quantified as the macroeconomic burden attributable to diseases. The proportion of disease burden attributed to dietary risk factors was quantified using population-attributable fractions derived from the global burden of disease study 2019, which was integrated into the health-augmented macroeconomic model. Estimates were converted to 2017 international dollars (INT $). - Results - The estimated global macroeconomic burden attributable to dietary risks from 2020 to 2050 was INT $15,491 [uncertainty interval 13078, 18742] billion, representing 0.34% (uncertainty interval 0.29%, 0.41%) of the total gross domestic product. The macroeconomic burden was unevenly distributed across countries, regions, income groups, disease types, and dietary risk factors. The United States (INT $3972 billion), China (INT $2764 billion), and India (INT $1300 billion) had the largest macroeconomic burden. Ischemic heart disease (INT $9384 billion), diabetes (INT $2392 billion), and stroke (INT $1954 billion) accounted for ∼90% of the overall macroeconomic burden. A diet low in whole grains (INT $3808 billion) incurred the highest cost, followed by a diet high in sodium (INT $2812 billion) and red meat (INT $2337 billion). - Conclusions - The global macroeconomic burden attributable to dietary risks was substantial and varied across countries, regions, income groups, disease types, and individual dietary risk factors.
Gesehen am 20.10.2025